Changes in the nutrients, phytochemical profile and antioxidant activity of Rheum officinale Baill. leaf blades during different growth periods - Dai, Lixia; Miao, Xiaolou; Ma, Yudong; Yang, Xiaorong; Li, Bing; He, Jian; Wang, Yu; Dong, Pengcheng; Zhang, Jiyu; Shang, Xiaofei (Frontiers in Nutrition, 2024)
Rhubarb contains an abundance of compounds and nutrients that promote health through various activities; however, these activities are affected by the harvest season. In this paper, the changes in nutrients, phytochemical profiles and antioxidant activity of Rheum officinale leaf blades (LRO) during different growth periods were investigated. The results showed that LRO is a good source of protein, fiber, and minerals and contains abundant fatty acids; however, as the harvest time increased from March to July, the levels of protein and amino acid decreased, and the levels of other nutrients reached a maximum in May or June. LRO also contains flavonoids, terpenoids, and quinones. As the harvest time increased, the quinone content decreased, possibly due to the unstable chemical properties of quinones at high temperatures. The flavonoid contents reached a maximum in May or June. This study indicated that LRO is a source of nutrients and chemical components and can be used for functional food production. In addition, the nutrients and chemical components related to the antioxidant activity of LRO changed according to the harvest season.